Advantages of promoting a product to the market with the help of event marketing - Tkacheva, N. P.; Pererva, P. G.; Kosenko, S. A. (Видавничий дім "Києво-Могилянська академія", 2023)
At the heart of event marketing is an event - real or fictional, organized specifically for a specific campaign. It is in conjunction with the event that a set of proposals is considered, which should lead to the desired marketing result. To be associated with the event, that is, to be a part of it and, at the same time, to have a direct benefit from the event, promoting the interests of the company - this is the philosophy of event marketing, expressed in two words: "to be" and "to have".
Переваги просування товару на ринок за допомогою подієвого маркетингу
Keywords: event marketing; promotion; products; market; enterprises